Asuhan Kebidanan Pada Ibu Nifas Dengan Luka Laserasi Perineum Di PMB Dewi Sartika Wilayah Kerja Puskesmas Kuok - Lestari, Silvi; Mayasari, Endang (Evidence Midwifery Journal, 2024)
A perineal wound is a tear that occurs in the perineal area spontaneously or deliberately by cutting (episiotomy) to make the birth of the baby easier. Efforts to care for perineal wounds are very important to prevent infection in the perineal wound. Acceleration in wound healing is highly expected, one of which is by consuming high protein, namely eggs. This research aims to provide care to postpartum mothers with perineal wounds at PMB Dewi Sartika in the working area of ??the Kuok Community Health Center in 2024. This research is in the form of a case study with a descriptive observational method carried out on Ny. A at PMB Dewi Sartika on July 4-10 July in 2024. The results of the case study research given to Ny. A namely three visits over 1 week. The midwifery care provided is in the form of counseling on how to care for perineal wounds, teaching mothers personal hygiene in the perineum and genitalia area, giving mothers eggs to boil and consume twice every day. Based on the care given to Ny. A In conclusion, the care provided was carried out well and produced positive results. It is hoped that this research can become a reference for readers, researchers and increase insight and develop knowledge regarding care for postpartum mothers with perineal wounds.